Stakeholder Salience for Stakeholder Firms: An Attempt to Reframe an Important Heuristic Device - Ali, Mohammad A. (Journal of business ethics, 2017)
This work underscores the importance of answering the question: who are organizational stakeholders? It argues that stakeholder theory is a normative management theory, and there is a need to differentiate between stakeholder and non-stakeholder firms. It further argues that the overall organizational stakeholder orientation indicates how narrowly or broadly organizations define their stakeholders. Therefore, this work attempts to provide a stakeholder salience scheme for stakeholder organizations, i.e., organizations with accommodative and proactive stakeholder orientations. In the process, this work reviews key scholarly contributions and points out some potential weaknesses in these contributions with an aim to develop a new stakeholder typology. This work contributes to the existing literature by: introducing a contingent variable, i.e., organizational strategy, in a stakeholder typology scheme; reaffirming the normative aspect of stakeholder theory by placing normative considerations at the center of stakeholder salience typology; and improving the descriptive validity of stakeholder theory by adding a new stakeholder variable, i.e., organization, in the presented stakeholder salience typology scheme.